Trinuclear Mixed-valent Manganese Complex with Non-schiff-base Tetradentate Ligand Showing a Ferromagnetic Coupling - Masahiro Mikuriya; Iyo Matsushima; Daisuke Yoshioka (Chemistry Journal of Moldova: General, Industrial and Ecological Chemistry, 2017)

(untitled)
Mixed-valent trinuclear manganese complex with N,N’-bis(2-hydroxy-3,5-dimethylbenzyl-N,N’-dimethyl-1,2-ethanediamine (H2hdde), [Mn3(hdde)2(CH3CO2)2(CH3O)2], was synthesized. The X-ray crystal structure analysis revealed a linearly arrangement of MnIII-MnII-MnIIIcore, where a ferromagnetic coupling (J = 2.62 cm–1) between the MnIII and MnII ions.